CYTOMEGALOVIRUS: A TALE OF RESISTANCE - Janković, Marko G; Jovanović, Tanja (Medicinski podmladak, 2019)
Cytomegalovirus (CMV) is a pathogen that affects the majority of the world’s population. It may exhibit a wide spectrum of clinical manifestations, ranging from asymptomatic infection in the healthy, congenital disease of the newborn to downright life-threatening illness in the immunocompromised. Initiating timely and adequate therapy can prove lifesaving. At times the virus develops resistance to specific drugs, an occurrence that can lead to the patient’s demise. This mini-review explores the molecular aetiology and incidence of resistance, the antiviral arsenal that is at our disposal, as well as the diagnostic approaches to uncovering drug resistance.